2012
DOI: 10.1007/s00442-012-2262-7
|View full text |Cite
|
Sign up to set email alerts
|

Assembling an ant community: species functional traits reflect environmental filtering

Abstract: Species should only persist in local communities if they have functional traits that are compatible with habitat-speciWc environmental conditions. Consequently, pronounced regional environmental gradients should produce environmental Wltering, or a trait-based spatial segregation of species. It is critical to quantify the links between species' functional traits and their environment in order to reveal the relative importance of this process to community assembly and promote understanding of the impacts of ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 61 publications
4
100
0
1
Order By: Relevance
“…Moreover, a lower residence time of O. chelifer colonies may also decrease benefits provided by these aggressive ants through protection against insect herbivory to seedlings (see Passos and Oliveira 2004). More exposed sandy soils at edges of cerrado may reach extreme temperatures, possibly over the thermal tolerance of these ants (Wiescher et al 2012). Thus, although ant nests seem to be safe sites for seedling establishment in the interior of cerrado, this potentially beneficial effect disappears near edges.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, a lower residence time of O. chelifer colonies may also decrease benefits provided by these aggressive ants through protection against insect herbivory to seedlings (see Passos and Oliveira 2004). More exposed sandy soils at edges of cerrado may reach extreme temperatures, possibly over the thermal tolerance of these ants (Wiescher et al 2012). Thus, although ant nests seem to be safe sites for seedling establishment in the interior of cerrado, this potentially beneficial effect disappears near edges.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, water stress is among the main mechanisms promoting seedling mortality worldwide (Moles and Westoby 2004). Environmental conditions may also filter the local ant assemblage following physiological, morphological, or behavioral traits of the ants better adapted to the harsh conditions found at edges (Wiescher et al 2012). Furthermore, other factors not directly related to microclimate such as resource availability, competition, and predation risk may also influence the diversity and activity of ants, thus influencing the ant species likely to interact with fallen fruits of Erythroxylum at edges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the arthropods, ants are an ideal taxonomic group for investigating relationships between morphology, traits, and assemblage structure because they (i) are abundant, comprising the dominant fraction of animal biomass in most terrestrial ecosystems (Wilson and Hölldobler, 2005), (ii) perform a range of important ecosystems functions (Del Toro et al 2012), (iii) exhibit a very large morphological diversity at very small scales (Silva and Brandão 2010), and (iv) vary in composition along environmental gradients (Gotelli and Ellison 2002). In addition, many studies have shown that ant species have specific traits that are correlated with environmental conditions (Wiescher et al 2012), macro-or microhabitat structure (Kaspari and Weiser 1999, Gibb and Parr 2010, Yates et al 2014) and resource exploitation (Retana et al 2015). Finally, recent research with stable isotopes has identified 5 morphological space occupied by temperate and tropical ant assemblages.…”
mentioning
confidence: 99%
“…This was unlike those of type (4) in the locality of Notto, which grew fruits for the export market and displayed higher intensification levels (Ndiaye et al, 2012). The weak or non-existent technical interventions in type (1) and type (2) orchards were conductive to high leaf litter levels, no pesticide use and no fertilizer inputs that influenced ant diversity, ant richness or ant community structure, as reported by other studies demonstrating the sensitivity of ants to environmental conditions (Peck et al, 1998;New, 2000;Hernández-Ruiz and Castaño-Meneses, 2006;Torchote et al, 2010;Chen et al, 2011;Wiescher et al, 2012;Bernadou et al, 2013). For the group (A) orchards, one ecological factor able to influence the ant community was the vegetation stratum which determines the amount of leaf litter (Perfecto and Snelling, 1995;Ellison et al, 2002;Boulton et al, 2005), depending on whether or not there was orchard cleaning.…”
Section: Ant Community Structure Depending On the Locality And The Ormentioning
confidence: 62%